2011
DOI: 10.1645/ge-2540.1
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey of Encephalitozoon cuniculi Infection in Japanese Dogs

Abstract: Antibodies to Encephalitozoon cuniculi were examined by enzyme-linked immunosorbent assay using E. cuniculi PTP2 recombinant protein and by Western blot analysis on a total of 472 dog serum samples that had been collected in Japan. Of these samples, 21.8% (103/472) had antibodies against E. cuniculi. Each of 5 serum samples that showed high (>1.0) or low (<0.1) OD value was selected randomly and further examined by Western blot using E. cuniculi-native antigens. All samples with high OD values reacted with spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Similar to studies in Japan (Sasaki et al. ) and Poland (Piekarska et al. ), a low prevalence of E. cuniculi (2.1%) within the investigated population of dogs was observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to studies in Japan (Sasaki et al. ) and Poland (Piekarska et al. ), a low prevalence of E. cuniculi (2.1%) within the investigated population of dogs was observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…E. cuniculi infections of pet rabbits and laboratory rabbits are best described (for review see (Künzel and Joachim, 2010)). However this species can also infect several other mammals (Wasson and Peper, 2000, Levkutová et al., 2004, Mathis et al., 2005, Goodwin et al., 2006, Lindsay et al., 2009, Sasaki et al., 2011, Wagnerová et al., 2012, Cray and Rivas, 2013, Meng et al., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…One author reported that the potential role of cats in the transmission of the infectious agent cannot be excluded [14]. In Japan, a seroepidemiological survey of E. cuniculi infection in domesticated dogs and domesticated rabbits has been performed [7,16], but the prevalence of E. cuniculi infections in cats has not been reported. E. cuniculi in subclinically infected cats may represent a reservoir and potential risk for immunocompromised patients [11,12].…”
mentioning
confidence: 99%
“…Testing for antibodies against E. cuniculi was performed using an enzyme-linked immunosorbent assay (ELISA) with glutathione S-transferase fusion polar tube protein 2 as the antigen [16]. Individual cat serum samples diluted to 1:400 and horseradish peroxidase-conjugated goat anti-feline immunoglobulin G antibody (MP Biomedicals, Santa Ana, CA, U.S.A.) diluted to 1:10,000 were used as the first and second antibodies, respectively.…”
mentioning
confidence: 99%